Immune Conversion of Tumor Microenvironment by Oncolytic Viruses: The Protoparvovirus H-1PV Case Study - Marchini, Antonio; Daeffler, Laurent; Pozdeev, Vitaly I.; Angelova, Assia; Rommelaere, Jean (Frontiers in Immunology, 2019)
Cancer cells utilize multiple mechanisms to evade and suppress anticancer immune responses creating a “cold” immunosuppressive tumor microenvironment. Oncolytic virotherapy is emerging as a promising approach to revert tumor immunosuppression and enhance the efficacy of other forms of immunotherapy. Growing evidence indicates that oncolytic viruses (OVs) act in a multimodal fashion, inducing immunogenic cell death and thereby eliciting robust anticancer immune responses. In this review, we summarize information about OV-mediated immune conversion of the tumor microenvironment. As a case study we focus on the rodent protoparvovirus H-1PV and its dual role as an oncolytic and immune modulatory agent. Potential strategies to improve H-1PV anticancer efficacy are also discussed.